1998
DOI: 10.1002/(sici)1099-0739(199805)12:5<361::aid-aoc731>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Particle size control and optical properties of laser-synthesized silicon nanopowders

Abstract: Silicon nanoparticles have been synthesized by heating reactant gases with a 500 W CO2 laser. A technique based on scattering of He–Ne laser light by particulates in a reaction flame has been developed for probing the particle size evolution during the process, in order to scale down the particle diameter (under 10 nm). The optical and structural properties of laser‐synthesized silicon nanopowders obtained in different runs are reported. © 1998 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The production of hydrogen terminated silicon (Si) nanoparticles is currently an area of intense research. The primary methods of producing large amounts of hydrogen terminated Si is either from the mechanical fracturing of porous Si or the gas-phase decomposition of silane or organosilane gas. In both cases, further etching is necessary using nitric and hydrofluoric acid to produce a stable, well-passivated hydrogen surface . Once the surface is hydrogen passivated, further functionalization via hydrosilation is possible .…”
mentioning
confidence: 99%
“…The production of hydrogen terminated silicon (Si) nanoparticles is currently an area of intense research. The primary methods of producing large amounts of hydrogen terminated Si is either from the mechanical fracturing of porous Si or the gas-phase decomposition of silane or organosilane gas. In both cases, further etching is necessary using nitric and hydrofluoric acid to produce a stable, well-passivated hydrogen surface . Once the surface is hydrogen passivated, further functionalization via hydrosilation is possible .…”
mentioning
confidence: 99%
“…The influence of synthesis parameters on silicon characteristics has been studied in previous work. Botti and co‐workers investigated the influence of reactor pressure and silane dilution percentages on particle size using transmission electron microscopy (TEM) and small‐angle neutron scattering (SANS) . Wang et al carried out research on the influence of laser intensity, SiH 4 flow, and chamber pressure on silicon nanoparticle size in both theory and experiment .…”
Section: Introductionmentioning
confidence: 99%
“…Among the synthesis techniques, the CO 2 laser synthesis has proved to be efficient for the production of photoluminescent size selected silicon nanoparticles [2] with very high quantum efficiency [3]. Using a continuous CO 2 laser, silicon nanopowders were also obtained by several groups [5,1], and thermal and/or chemical treatments are necessary to obtain photoluminescence properties. It was shown that the photoluminescence properties originate from quantum confinement effects without any contribution from interaction between particles [4].…”
Section: Introductionmentioning
confidence: 99%